Sixteenth‐mode substrate integrated waveguide cavity filters. Issue 9 (15th December 2018) - Azad, Amit Ranjan; Mohan, Akhilesh
Abstract: This paper presents bandpass filters using sixteenth‐mode substrate integrated waveguide (SMSIW) cavities operating at fundamental mode TM010 . The first filter is a single‐layer fourth‐order bandpass filter which exhibits compact size, good selectivity and wide‐stopband up to 2.25 f 0 . The stopband rejection is restricted due to the presence of the passband generated by the higher‐order mode TM020 . To further reduce the size and improve the stopband characteristic of the filter, a multilayer configuration is proposed. The second filter is a multilayer second‐order bandpass filter in which the two cavities are coupled through a circular arc‐shaped slot etched on the ground plane of the cavities. The position and the dimensions of the slot are adjusted to obtain the desired couplings of TM010 and TM020 modes. The passband is created by TM010 mode, and its bandwidth can be controlled by realizing the desired TM010 coupling. Moreover, the passband constituted by TM020 mode is suppressed by minimizing the coupling of TM020 mode, and a stopband up to 3.14 f 0 is obtained which is wider than that of the first filter. The proposed filters have the advantages of compact size, low loss, and wide‐stopband performance. The filters are designed, fabricated and measured. The simulation and measurement results show an acceptable agreement.